Prayer, Liturgy, and Sacramentality: The Doctrine of Theosis as Key to Bridging Obstacles to Orthodox–Pentecostal Dialogue and Unity - Monge, Rico G. (2025)
This essay argues that some of the biggest impediments to Orthodox–Pentecostal understanding (liturgical prayer and sacramental rituals) disappear when interpreted through the soteriological lens of the doctrine of theosis. In the spirit of ecumenical dialogue, the author articulates the doctrine of theosis primarily through biblical texts and concepts introduced by twentieth-century Protestant theologians and philosophers Paul Tillich and Paul Ricoeur, rather than a heavy reliance on patristic sources or contemporary Orthodox theologians. In articulating this core concept in Orthodox soteriology, the author contrasts it with both the Roman Catholic and common Protestant notions of ‘justification’, demonstrating that theosis is incompatible with the concepts of faith aided by ‘meritorious works’ and ‘imputed righteousness’ conferred by ‘faith alone’, respectively. Rather, theosis is a Spirit-filled way of life made possible by praxis of the kind of faith (‘apart from works of the law’) defined in chapters 11 and 12 of the Epistle to the Hebrews.
Keywords: Ecumenical Dialogue; Sacraments; Liturgy; Theosis; Eastern Orthodoxy; Pentecostalism